Aplasia cutis congenita with dystrophic epidermolysis bullosa: clinical and mutational study. (April 2014) - Chiaverini, C.; Charlesworth, A.; Fernandez, A.; Barbarot, S.; Bessis, D.; Bodemer, C.; Bursztejn, A.‐C.; Cobo, A.‐M.; Del Rio, M.; D'Incan, M.; Labrèze, C.; Langlet, C.; et al.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Aplasia cutis congenita (ACC) has been associated with all clinical forms of inherited epidermolysis bullosa (EB), including dominant and recessive dystrophic EB (DEB). To date, only a few patients with DEB specifically combined with ACC have been described and genotyped and almost all cases represent dominant forms of the condition. What does this study add? Our findings suggest that ACC is a frequent manifestation in patients with DEB irrespective of the severity of the disease and is due to leg rubbing in utero. In children with a moderate form of DEB with no or moderate skin fragility, a glycine substitution near the triple helix domain interruption domain of the collagen VII leading to thermolabile protein could explain this phenomenon.